2019
DOI: 10.1021/acs.jced.9b00116
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Mixed Ternary Systems of Hexafluoridosilicate Salts (M = Na+, K+, or NH4+) in Hexafluoridosilicic Acid Aqueous Solutions at T = 353.15 K

Abstract: The solubility of hexafluoridosilicate salts and acid aqueous solutions {yH 2 [SiF 6 ] + (1 − y)M 2 [SiF 6 ]}(aq) with Na + , K + , and NH 4 + was experimentally determined at various ionic strength fractions (y) with y = 0.20, 0.50, and 0.80 at the temperature 353.15 K. The precipitated solid phases obtained by filtration were characterized by X-ray diffraction, which show only the presence of a single crystalline form for each ternary system at various (y) values, Na 2 [SiF 6 ], K 2 [SiF 6 ], or (NH 4 ) 2 [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…12−15 The solubility of potassium (sodium) fluorosilicate in phosphoric−sulfuric acid was measured, and it was found that the solubility decreases with the reduction of temperature and increase of fluorosilicic acid concentration. 16 Skafi et al 17 and Frayret et al, 18 1. All of the chemicals were used without further purification, and deionized water (18.2 MΩ cm) was used in all of the experimental runs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12−15 The solubility of potassium (sodium) fluorosilicate in phosphoric−sulfuric acid was measured, and it was found that the solubility decreases with the reduction of temperature and increase of fluorosilicic acid concentration. 16 Skafi et al 17 and Frayret et al, 18 1. All of the chemicals were used without further purification, and deionized water (18.2 MΩ cm) was used in all of the experimental runs.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, literature data on K 2 SiF 6 were available only in water. The solubility of potassium (sodium) fluorosilicate in phosphoric–sulfuric acid was measured, and it was found that the solubility decreases with the reduction of temperature and increase of fluorosilicic acid concentration . Skafi et al and Frayret et al., respectively, measured the solubilities of three alkaline salts of hexafluorosilicate (K 2 SiF 6 , Na 2 SiF 6 , and (NH 4 ) 2 SiF 6 ) in different acidic (hydrofluoric, hydrochloric, phosphoric, and nitric acids and hexafluoridosilicic acid) solutions. Besides, Wang et al found that the solubility values of K 2 SiF 6 increased with increasing temperature, whether in water, pure fluoride solution (H 2 SiF 6 +HF+H 2 O), or phosphoric acid digestion liquor.…”
Section: Introductionmentioning
confidence: 99%